"La solidaridad no perece": Community organizing, political agency, and mutual aid in Puerto Rico. Issue 3 (27th May 2022) - Santiago Ortiz, Aurora; Navarro Pérez, Antonio; Agosto Ortiz, Paulette; Cruz González, Coralis; Román Oyola, Michelle
Abstract: In the wake of Hurricane Maria and in response to the negligent inefficiency of the local and federal governments, community groups and collectives, grassroots organizations, and activists of multiple causes began organizing under the principles of mutual aid and solidarity in Puerto Rico. One of these is the Colectivo Casco Urbano de Cayey (CCUC), a community organization comprised of local activists and community leaders, undergraduate students, and a professor. This essay brings together four members of the collective in a dialogue where they reflect on the central role of solidarity in the CCUC's organizing and projects and the ways solidarity operates as a praxis of self-determination in the face of neoliberal austerity measures in Puerto Rico. We also highlight the relational work that was done prior to establishing the CCUC that enabled its creation. We also discuss how we negotiate our collaborative relationship across difference through critical dialogue and reflection, the challenges that arise because of our colonial subjectivities, and the ways we circumvent colonial logics through other ways of being and relating anchored in solidarity and interdependence.